(untitled) (Cultura Económica, 2019)
This article analyses the problems generated by the interaction of man with the environment over the centuries and with population growth. The discussion that this generates about individual rights, property, government interference and its increase imposes the need to generate an acceptable, consensual and logical doctrinal framework that regulates it, preserving the autonomy of the will and considering the evolution and technological progress. Likewise, the article mentions different relevant contributions of various authors in the course of the evolution of economic thought.